Guidelines for the organization of headache education in Europe: the headache school II - Jensen, Rigmor (Springer Milan, 2010)
In order to promote education on headache disorders, European Headache Federation (EHF) in conjunction with National Headache Societies organizes educational courses meeting uniform standards according to previous published guidelines. Based on six headache summer schools’ experience, an EHF subcommittee has reviewed these guidelines, and here the revised version is presented. The goals remain the same: quality courses that will attract physicians and neurologists seeking to increase their knowledge, skills, and understanding in the area of primary and secondary headache. Detailed guidelines, a day-to-day program, and a multiple-choice test battery have now been outlined. It is recommended to include practical sessions with patient interviews and hands-on demonstrations of non-pharmacological treatment strategies. For countries that want a ‘low cost’ education program, a Video School program of a similar scientific standard has been developed. To be certified for CME credits, patronage, and financial support from EHF, it is highly recommended to adhere to the suggested teaching strategies. We hereby aim to promote and professionalize the education in headache disorders and endorse the educational courses meeting uniform standards of excellence.